Handmade: A Critical Analysis of John of Damascus’ Justification for Venerating Icons - Rhodes, Michael Craig (Heythrop journal, 2013)
The essay is an analysis of John of Damascus’ justification for venerating the icons. Under the subtitle ‘reasoning for venerating the icons’ the essay conducts the analysis in three parts. First, John's definition of ‘veneration’ is presented and examined. Second, the OT ‘veneration’ passages he cites are critically evaluated. Third, the apparent incoherence of John's case is demonstrated from the Eastern Orthodox notion of scripture. This is a follow-up study to a previous essay (i.e., ‘Handmade: a critical analysis of John of Damascus’ reasoning for making icons’) which analyzes a problem in Orthodox aesthetics closely related to the one I examine here.